Resolution enhancement of ultrasonic imaging at oblique incidence by using WTFM based on FMC-AR. (October 2021) - Shi, S.Q.; Lin, L.; Luo, Z.B.; Sun, X.; Jin, S.J.
Highlights: WTFM is developed to improve ultrasonic imaging resolution at oblique incidence. The scatterers with 0.7 λ central distance are identified by WTFM. Knowledge-based method and weighted imaging is beneficial to enhance robustness. Abstract: Image resolution is the key criterion for evaluating ultrasonic imaging quality. However, the smaller time difference between scattered waves and the mutual occlusion of scatterers restrict the resolution enhancement at oblique incidence. In this paper, the weighted total focusing method (WTFM) based on the full matrix capture data processed by autoregressive spectrum extrapolation (FMC-AR) is presented to improve the image resolution at oblique incidence to subwavelength-scale from wavelength-scale. The AR parameters are determined by the knowledge-based method for improving applicability. Meanwhile, the weighted TFM imaging with different effective frequency bands is applied to extract and highlight the target characteristics, enhancing the robustness of the proposed method. The simulated and experimental results demonstrate that the side-drilled holes (SDHs) with 0.7 λ (wavelength λ ) central distance can be identified with accurate location by WTFM. Finally, the effects of AR order and effective frequency band on WTFM image are analyzed by experiments.